The influence of diesel pilot injection timing on the combustion and emission characteristics of a natural gas-diesel dual-fuel engine - Wu, Yue; Qiu, Tao (Frontiers in Mechanical Engineering, 2025)
This study investigated the effects of varying diesel pilot injection timings (19°–25° BTDC) on the thermal efficiency, combustion, and emission characteristics of an engine operating under different load ranges (25%–100%) using a modified single-cylinder natural gas-diesel dual-fuel (NDDF) engine. The results indicate that advancing the injection timing can significantly improve brake thermal efficiency (BTE) under partial loads (25%–75%), but efficiency decreases at 100% load. Specifically, advancing the timing to 25° BTDC results in a reduction in BTE compared to 23° BTDC. This suggests that the negative compression work generated by excessively early combustion exceeds the benefits from improved combustion, thereby establishing a physical limit for advanced injection under high-load conditions. Combustion analysis identified a distinct “combustion phase shift” phenomenon. The results show that although advanced injection shifts the combustion phase closer to the favorable high-temperature region near top dead center (TDC), there is only a slight change in combustion duration. This is mechanically attributed to the over-leaning of the pilot diesel spray during prolonged ignition delay. The consequent formation of weak combustion cores slows initial flame propagation, counteracting the accelerating effects of improved thermodynamics. Emission analysis reveals a trade-off: advanced injection reduces smoke emissions by up to 4.2% but substantially increases nitrogen oxides (NOx). Concurrent increases in carbon monoxide (CO) with advanced timing suggest local quenching and over-leaning effects. Additionally, a dynamic fuel substitution strategy was employed to optimize the NDDF engine, successfully maintaining efficiency while mitigating detonation. This study provides a validated experimental basis for the precise calibration of dual-fuel engines across the load range.